Low-energy electron scattering cross sections for nanoscale water clusters - Katinka Horn; Svetlana Tsizin; Loren Ban; Egor Chasovskikh; Bruce L. Yoder; Francesca Calegari; Ruth Signorell (Physical Review Research)
Electron scattering cross sections are essential for the quantitative description of electron-induced processes in nanoconfined aqueous systems. Here we report on energy- and size-dependent cross sections for water clusters with diameters between ∼1.0 and 2.5 nm and electron energies below ∼32 eV. The cross sections of the clusters are up to a factor of 2 larger than those of water, suggesting a reduced dielectric screening in nanoconfinement. The cross sections show no significant cluster size dependence. A slight increase of cross sections with increasing electron energy is attributed to the increasing contribution from electronic scattering channels. As the simplest form of nanoconfined water, nanoscale water clusters represent an important model system.